2009
DOI: 10.1590/s0100-736x2009000800005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação radiográfica da cobertura acetabular à cabeça femoral, após osteotomia tripla e aplicação de cunha sacroilíaca, em pelve de cadáveres de cães

Abstract: Pesq. Vet. Bras. 29(8):625-631, agosto 2009 RESUMO.-Na tentativa de evitar algumas das dificuldades associadas à osteotomia pélvica tripla (OPT), foi desenvolvido experimentalmente o método de aplicação de cunha na junção sacroilíaca para aumentar a ventroversão acetabular. O objetivo deste estudo foi aplicar as técnicas de cunha sacroilíaca e OPT em cadáveres e avaliar radiograficamente a eficácia da ventroversão acetabular. Para tal, foram utilizados 10 cadáveres de cães, adultos, com 15-25 kg. Em cada he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 13 publications
1
11
0
2
Order By: Relevance
“…Once the sacroiliac joint was sectioned, a 2.5-mm bore was made on the lateral surface of the sacrum using a surgical drill, with the depth being 50% to 60% of that of the sacral body. Simultaneously, the wedge was positioned at the sacroiliac junction, with its base level with the dorsal plane of the sacrum, as described by Regonato et al (2009) (Fig.1A).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Once the sacroiliac joint was sectioned, a 2.5-mm bore was made on the lateral surface of the sacrum using a surgical drill, with the depth being 50% to 60% of that of the sacral body. Simultaneously, the wedge was positioned at the sacroiliac junction, with its base level with the dorsal plane of the sacrum, as described by Regonato et al (2009) (Fig.1A).…”
Section: Methodsmentioning
confidence: 99%
“…In a study with canine corpse pelves, Conzemius et al (1999) proposed the use of SW, producing an effect similar to that of TPO. Regonato et al (2009) demonstrated the surgical approach, and proved its efficiency for acetabular ventroversion, using castor bean (Ricinus communis) polyurethane wedges in canine corpses. This technique, besides promoting acetabular ventroversion, overcame the disadvantages of TPO, reducing surgical time, risks, and costs.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations